Iwasawa cohomology of analytic (φL, ΓL)-modules - Steingart, Rustam (Acta arithmetica, 2024)
We show that the coadmissibility of the Iwasawa cohomology of an L-analytic Lubin-Tate (φL,ΓL)-module M is necessary and sufficient for the existence of a comparison isomorphism between the former and the analytic cohomology of its Lubi